Caderno de leitura literária : a recepção pelo olhar de gênero - Menezes, Meiryelle Paixão (2015)
This Work Course Completion (TCF) is composed of a dissertation and part of an educational notebook with literary workshops. The goal was to develop a practice of literary reading focused on the interpretation of youth tales through the eyes of gender studies. For this, a focused search for the reading and interpretation of literary texts in the school environment emphasizing a reflection on the gender representation of the princes and princesses of folktales was applied. Such research was carried out in a state school from Sergipe with 6th grade students and intended to reduce the gender bias that is still part of the relations between boys and girls, who repeated sexist and macho patterns came from the male domination. The reading lessons of literary texts were aimed at the exploration of gender issues in the imagination of fairy tales. These relationships are based on the common sense to the repetition of prejudice against women. In this context, a job offer with reading workshops of literary tales “Entre a espada e a rosa”, “A moça tecelã” and “Como um colar” by Marina Colasanti was applied, in order to improve the reading levels of / the students and make them aware of the gender discrimination at school. After the various stages of this research, it was proposed the literary reading Notebook: receiving genre for elementary school as a teaching material built from that experience. Methodologically, the research application was divided into four stages: 1 - the formation of the reader, which was discussed by the perspective of U. Eco; 2 - the Reading methods A. Rouxel, Aguiar and Bordini and C. Gomes; 3 - the gender approach by the perspective of P. Bourdieu, G. and E. Laurel Xavier; and 4 - the data analysis. During these workshops, a data collection was made about the reading and discussion of the differences between male and female identities in receiving the wonderful tales. After the implementation of reading workshops, there was the construction of the literary reading book that summarizes the main stages of the approach developed in this research. With this book, we hope to contribute to the formation of readers and critics in order to raise awareness of the students with regard to gender discrimination, and form a more just and egalitarian society.